De Landschapsarchitectuur van het Polder-boezemsysteem - Bobbink, Inge (A+BE | Architecture and the Built Environment, 2016)
The Dutch lowlands is an artificial landscape, created as a result of the wish to regulate the water that dominated the topography in the Delta. This ‘confined’ lowland water, the polder-boezem system12, features an enormously diverse range of water structures and forms, which largely dictates the spatial planning of the lower Netherlands. This dissertation concerns the polder-boezem system, a water system that was created by trial-anderror, has been adapted continually and now needs to be expanded to cope with the effects of climate change. The research focuses on answering the following question: What potential does the current polder-boezem system have, with the help of landscape architectonic design, to define (or redefine) the spatial identity of the lowlands? So that the lowland water can be discovered (or rediscovered) and reinforced as the spatial and compositional power of the (urban)landscape (chapter 1). The research into the landscape and landscape-architectonic quality and the potential contained within the polder-boezem system was carried out by reviewing drawings of both existing and self-produced charts (the overlay technique). The 4-form layer analysis method was used for the landscape-architectonic research. This research method, which was developed by the Chair of Landscape Architecture of the Faculty of Architecture and the Built Environment at TU Delft, reveals the design tools for a design. The research showed that it can also be used to analyse a man-made (cultural) landscape (chapter 2). The water vocabulary that has been illustrated and described introduces, as the basic premise for the research, the water-technical role and position of all the water elements that combine to make up the water system (chapter 3). The boezem water as a cohesive network was illustrated on the basis of this inventory, and the polder water was analysed using a cut-out of the area under study (chapters 4 and 6). The boezem network map, drawn on the scale of the study area (northern Noord-Holland and the Randstad), generated insight into the relationship between the structure and design differences and the situational context of the boezem network for the landscape research. The structure and form differences in the boezem sections can be explained by the landscape types in which they are found - the sand ridge landscape (1), the river landscape (2), the marine clay landscape (3) and the peat bog landscape (4) - and the landscape layers to which they belong - natural landscape (1), man-made (cultural) landscape (2) and urban landscape (3). The original natural boezem sections, in particular, are unique to the area, and express the genius loci, the spatial identity of the location. They form the longest boezem structures in the Delta, are the main carrier of the network and have a perceivable ‘sphere of influence’. These areas with a recognisable identity are called boezem landscapes in the dissertation. They ultimately determine the context for the landscape-architectonic design of the water system (chapter 5). Prior to the landscape-architectonic research, carried out on the scale of a single boezem area, the term landscape-architectonic quality for every form layer was defined - the basic form (1), the programme form (2), the image form (3) and the spatial form (4). This was done on the basis of the 4-form layer analysis, a deconstruction method. The basic form of water has landscape-architectonic quality when the geometry of the water form corresponds with, or develops from, the original water form in the natural landscape and the way it has been adapted, which results in a decipherable, potent and ‘dramatised’ landscape-architectonic design. The programme form of water has landscape-architectonic quality when the water system that has developed from the natural landscape has a recognisable, comprehensible and visible structure and form that illustrates the negotium use that corresponds with, or develops into, the otium use. The image form of water has landscape-architectonic quality when the water image elements unite to form a clear, area-specific illustration that refers to the representation of nature and the relationship between nature, culture and urbanity. The spatial form of water has landscape-architectonic quality when the water that originates from the natural landscape, and the way it has been adapted, shows an articulated visual-spatial design in a cohesive sequence, as far as the eye can see. All the water elements in the study area that showed a degree of landscape-architectonic quality or landscape-architectonic potential were recorded on a conclusion chart, per form layer. The conclusion charts show the design tools used and those that could conceivably be used: the design strategies (1), the design technique (2) and the design elements (3). The qualities identified were used as the basis for recommendations for expanding the tools and reinforcing the landscape-architectonic composition of the boezem landscape (chapter 7). The specific features of each boezem area are expressed in the structure and form differences of the polder-boezem system and are based on the natural landscape. The cohesion of form within a boezem area serves as the basis for further transformation. The landscape-architectonic tools are specific to a boezem landscape but provide enough information to formulate recommendations for the polderboezem system as a whole. The best way to increase the landscape-architectonic quality of the polder-boezem system is to highlight the cohesion of the water system on the scale of the entire boezem landscape. The boezem system defines the spatial character of the system. This cohesion can be reinforced in the form of a link between boezem water and polder water, specifically in the lake bed polder landscapes, by means of the realisation of the water sequence - canal, mill or pumping station, outlet and boezem. The stronger the compositional cohesion between the water sequence and the other polder water in polder or water-level area, the stronger the cohesion of the system. The waterworks set the architectonic tone in the system and belong to the crucial details of the polder-boezem system. It isessential to give attention to the design and position of the waterworks as a visible and/or perceived spatial link between the various water-level areas. The network character of the water system provides countless opportunities to integrate existing and new ecosystems, nature developments and other water management challenges into the polderboezem system. This green-blue connection could give the water system a considerable boost and help it develop into the Novel Fine Dutch Waterscape. Experimental designs show how the design instruments that were detected can be used to allow the polder-boezem system to define (or redefine) the spatial identity of the lowlands (chapter 8).